REPRESENTING ISIS ACTIONS IN TELEVISION DOCUMENTARY: INTEGRATING STORYTELLING INTO MULTIMODAL DISCOURSE ANALYSIS - Saleh, Ali Abdullah; Sherwani, Kawa Abdulkareem (International Journal of Psychosocial Rehabilitation, 2020)
The rule of the Islamic State of Iraq and Syria’s ISIS in Iraq lasted three years, during which many new television shows represented its actions; however, only a few documentary programmes appeared in any detail or were formatted in episodes. This paper examines the television documentary ISIS Was Here, produced in 2017 by Rudaw Television, a Kurdish Channel based in Kurdistan Region of Iraq. The programme was broadcast in the Kurdish language, and intensively and systematically represented the actions of ISIS. The results of my analysis show how the programme conveyed the destructiveness of the radical organisation, and how ISIS misrepresents Islam. Through a Multimodal Discourse Analysis, and based on semiotic codes, I show how meaning is realized in this show through more than one semiotic code.